The effect of language use on the financial performance of microfinance banks: Evidence from cross-border activities in 74 countries - Sougand Golesorkhi; Roy Mersland; Rebecca Piekkari; Grigory Pishchulov; Trond Randøy (Journal of World Business, 2019)
This multi-year study examines the relationship between financial performance and language use, observing 405 partnerships between microfinance banks and their international financial partners in 74 countries. Drawing on language research in international business, we find that microfinance banks based in English-speaking, French-speaking, and Spanish-speaking countries have higher performance. Furthermore, the linguistic distance between the home country of a microfinance bank and the home country of its international partner(s) is negatively related to its financial performance. Our large-scale study confirms the effect of language use on organization-level financial performance and extends research on language in multinationals from intra-firm to inter-firm relationships.
Keywords: 650